Answer: a²+b² = -99/2
Step-by-step explanation:
Since we are given two equations, this equations will be solved simultaneously to get a² and b²
a³ - 3ab² = 47 ... 1
b³ - 3a² b = 52... 2
From 1, a(a² - 3b²) = 47...3
From 2, b(b² - 3a²) = 52... 4
Adding 3 and 4, we have;
a²+b²-3b²-3a² = 99 (note that a and b will no longer be part of the equations as they have been factored out)
a²+b²-(3b²+3a²) = 99
(a²+b²) -3(b²+a²)= 99
Taking the difference we have
- 2(a²+b²) = 99
a²+b² = -99/2
The GCF is 36 since 36 can go into 144 (:
x
The answeris equall to because they are the same #
Let's solve your equation step-by-step.
2x
/5 + 3 = x/10 - 1
Step 1: Simplify both sides of the equation.
2x
/5 + 3 = x/10 - 1
2/5x + 3 = 1/10x - 1
Step 2: Subtract 1/10x from both sides.
2/5x + 3 - 1/10x = 1/10x - 1 - 1/10x
3/10x + 3 = -1
Step 3: Subtract 3 from both sides.
3
/10x + 3 - 3 = -1 - 3
3/10x = -4
Step 4: Multiply both sides by 10/3.
(10/3) * (3/10x) = (10/3) * (-4)
x = -40/3